Observations on the associations between damaging and aggressive behaviors, related lesions, and their implications for the welfare of pigs in the grower-finisher period - Markland, Lucy; Díaz, Julia Adriana Calderón; Boyle, Laura Ann; Pessoa, Joana; van Staaveren, Nienke (Frontiers in Veterinary Science, 2025)
IntroductionPigs perform damaging and aggressive behaviors, but few studies investigated associations between behaviors and resulting lesions in intensive settings. We investigated such associations within and across production stages to understand implications for welfare, and interpreted cut-off values of behavior for use as warning signals.MethodsFour batches of 419 pigs each (n = 1,676 pigs) were followed on arrival to a commercial grower-finisher unit at 12 weeks of age until slaughter. Pigs had docked tails, were managed according to routine practice and housed in 48 mixed-sex groups in eight rooms [35(±2) pigs/pen; 6 pens/room/batch]. Ear and tail lesions were assessed when pigs arrived to grower stage I [24.9 ± 5.33 kg of body weight (BW)], after 2 weeks when transferred to grower stage II (33.3 ± 7.04 kg BW), and after 4 weeks when transferred to the finisher stage (60.2 ± 7.74 kg BW; 18 weeks of age). All occurrences of damaging (ear, tail, and flank biting) and aggressive behaviors were recorded for 5 min per pen from the week after pigs arrived for 11 weeks.ResultsHigh variability existed between pens for behaviors and percentage of pigs that developed new ear or tail lesions on arrival to grower II and finisher stage. There were significant correlations among the behaviors only within grower stage II (all behaviors: 0.65 ≤ rs ≤ 0.80, p < 0.05), while the only correlations across production stages were ear biting (grower II and finisher rs = −0.29, p < 0.05), flank biting (grower II and finisher rs = 0.70, p < 0.05), and aggression (grower I and II rs = 0.37, p < 0.05). This suggests a sensitive period during grower stage II but also that performance of behaviors changes over time. The frequency of ear and tail biting did not need to be high for new lesions to develop, but thresholds changed depending on stage, behaviors, and lesion type.DiscussionThis underscores the intricacies in developing cut-off values for warning signals and may relate to the cumulative effect of different risk factors. Thus, early identification and multifaceted management strategies tailored to specific pens are needed to address behaviors with adverse implications for pig welfare. This highlights the challenges and complexities of improving pig welfare within current intensive production settings.